Amazônia globalizada: da fronteira agrícola ao território do agronegócio – o exemplo de Rondônia - Ricardo Gilson da Costa Silva (Confins)
Brazilian Amazon experiences the impacts of capital and commodities globalization. Its geographical expression results on fragmentation of endogenous territorial coherence, imposing the logic of global business to quotidian places. In Rondônia State, the soybean agribusiness represents the capital advancement in rural areas, altering former forms of land use to global production areas. These courses result in territory fragmentation, now submitted to international capital logics and streams, alienating places, the land use and the control of their destiny. This is the geography configured in south Rondônia, where agribusiness regionalization and capital territorialization are conditioning territorial dynamics to globalization vectors.